TREN EATING OUT, KEGIATAN MEMASAK, DAN HUBUNGANNYA DALAM MENUNJANG POLA HIDUP SEHAT - Tanjaya, Delvin; Anggrianto, Christian (Jurnal VICIDI, 2021)
This study aims to understand the phenomena and trends of eating outside food and the adverse effects and understand the benefits of cooking and its relationship in supporting a healthy lifestyle. The research method used in this research is the literature review method, by examining various international, national journals and books on related topics. The results showed that the habit of eating out had many adverse effects, especially for health, with the lack of nutrients needed by the body and the amount of energy and content of sodium, fat, and other harmful substances. This can be corrected by adopting the habit of cooking because some of the analysis results show various advantages of doing cooking activities. These advantages are essential in forming a healthier lifestyle and are free from various chronic diseases that can be suffered later. Keywords: Health, food, nutrition, disease, healthy lifestyle